Nationwide study of the susceptibility of the Bacteroides fragilis group in the United States. - Tally, F P (1985)
A nationwide susceptibility survey of the Bacteroides fragilis group was continued at New England Medical Center in 1983. A total of 555 strains were obtained from eight centers in the United States. In addition to the nine antimicrobial agents studied in the two previous years, three other agents were added to the evaluation: cefamandole, cefuroxime, and cefonicid. The results for the strains tested with the original nine drugs in 1983 were compared with those for 1,292 isolates tested in 1981 and 1982. The most active beta-lactam drug was piperacillin, which had an 8% resistance rate. Cefoxitin resistance increased from 10% in 1982 to 16% in 1983. High rates of resistance to cefotaxime, cefoperazone, cefamandole, cefonicid, and cefuroxime were encountered. No metronidazole- or chloramphenicol-resistant isolates were found during the 3 years of the study. Susceptibility patterns varied at the eight hospitals: the outbreak of cefoxitin resistance reported in 1982 at New England Medical Center remitted, while a high clindamycin resistance rate was documented at one hospital in 1983. These data indicate the need for determining the susceptibility patterns for the B. fragilis group of organisms at each hospital.